Finite element modeling of square confined concrete columns with stainless steel and carbon steel under concentric load - Venesia S Samalloa; Bambang Piscesa; Heppy Kristijanto (Journal of Civil Engineering, 2026)
The use of conventional carbon steel in steel tube confined concrete (STCC) structures presents durability challenges, particularly in marine environments, due to corrosion susceptibility and high maintenance requirements. Stainless steel tube confined concrete (SSTCC) offers enhanced corrosion resistance and improved long-term performance compared to carbon steel tube confined concrete (CSTCC). This study aims to validate numerical simulations against experimental results by evaluating load–displacement and stress–strain responses, while considering the effects of surface contact sensitivity between the concrete core and steel tube, as well as initial imperfections within the shear band region. A three-dimensional nonlinear finite element analysis (3D-NLFEA) model was developed for square cross-section STCC columns. The numerical results demonstrate strong agreement with experimental data. The comparison of load–displacement curves shows an average discrepancy of 3.22%, while the stress–strain responses exhibit an average difference of 5.00%. Improved correlation was achieved by incorporating a 10% material reduction to represent initial imperfections in the shear band region and calibrated surface contact parameters, including a cohesive strength of 0.7 MPa, a uniaxial tensile strength of 1.0 MPa, and an internal friction angle of 15°. These findings confirm the capability of the proposed numerical model to accurately predict the structural behavior of square STCC columns and highlight the effectiveness of stainless steel confinement in enhancing structural performance.